Peningkatan Literasi Keuangan Keluarga melalui Pelatihan Digital Pasca Pandemi - Edi Tohidi; Edi Wahyudin; Adhivia Julian; Aditya Fauzi Samsuri (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic has had a significant impact on household economic stability in Indonesia. Many families have experienced a decrease in income, changes in consumption patterns, and limited access to formal financial services. In the post-pandemic period, the economic challenges faced by households have become increasingly complex, thus requiring enhanced literacy and skills in financial management, particularly those based on digital tools. This Community Service Program (PKM) aims to provide training in digital-based household financial management to communities in the partner area, in order to improve their ability to manage income, expenses, savings, and the wise use of digital financial applications. The implementation method includes an initial survey to assess participants' financial literacy levels, preparation of training modules, face to-face and online training sessions, as well as evaluation of participants’ improvement in knowledge and skills. The training materials cover topics such as household financial planning, debt and savings management, the use of digital wallets, financial recording applications, and basic understanding of micro-investments. The results of the program indicate that the training successfully increased participants’ understanding of basic financial concepts and improved their ability to use digital financial tracking applications. Participants also became more skilled in preparing family budgets, monitoring daily expenses, and identifying priority needs. Other positive outcomes include heightened awareness of the importance of saving and managing financial risk. This activity provides tangible contributions to fostering economic self-reliance among families in the digital era. Going forward, similar training programs are expected to be developed as sustainable initiatives, particularly for lower-middle income communities that are more vulnerable to economic shocks.